Rare-earth substitution in Bi4Ti3O12 system for potential application - Al-Amani, Umar (2013)
This paper reported the improvement of dielectric and ferroelectric properties in BIT system with regards to rare-earth substitution.The rare-earth elements with different ionic radius such as Nd and Sm were used to improvethe shortcomings in BIT system. It was found that the dielectric constant of Nd substitution abruptly increased of about 82%, when the content of rare-earth was increased from 0.25 to 1.0. In contrast, the increase of dielectric constant in Sm substitution system was fairly small, which is about 12% from 0.25 to 1.0. The obvious difference in dielectric constant particularly at 1.0 for both substituted systems can be explained by the relaxation of orthorhombic distortion and octahedral tilting in a layered structure. Compared with the BIT system, the remanent polarization of Nd substituted was improved by 35%, while that of Sm substituted was reduced to 55%. Several reasons to explain the reduction in polarization for Sm substituted system was also investigated.